(untitled) (Journal of Engineering, 2009)
A numerical investigation was conducted to study the effect of simulated ice accreted on airfoil aerodynamics performance. The simulated ice shapes were tested on NACA 0012 airfoil wing at different Mach numbers. The study includes the one of the famous types of ice accreted on the airfoils called the rime ice. The calculation of ice droplet trajectories was performed by solving the trajectories governing equations of the droplet using FVM. A numerical model based on staggered FVM is built up to solve the governing equations of a body fitted grid, trajectories equation, continuity equation and momentum equation using FORTRAN 97. The turbulence model of (k-ε) has been adopted in the programming to evaluate the turbulence effect. The program is valid for any type of 4 or 5 digits airfoil. The program is available to evaluate the rime ice accumulation. The pressure, lift, drag and pitching moment coefficients are computed and compared with that of clean case results. The program was run over different Mach numbers, to compare the results obtained at these Mach Numbers. The investigation of the work was tested on NACA 0012 in a range of angle of attack 0º to 6º, where stall starts at this angle of attack as demonstrated by the results. The results show that the severity of ice formation could be more dangerous with increasing the angle of attack or the Mach number.